2013
DOI: 10.1016/j.vaccine.2013.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics and colostrum/milk differentially affect neonatal humoral immune responses to oral rotavirus vaccine

Abstract: Breast milk (colostrum [col]/milk) components and gut commensals play important roles in neonatal immune maturation, establishment of gut homeostasis and immune responses to enteric pathogens and oral vaccines. We investigated the impact of colonization by probiotics, Lactobacillus rhamnosus GG (LGG) and Bifidobacterium lactis Bb12 (Bb12) with/without col/milk (mimicking breast/formula fed infants) on B lymphocyte responses to an attenuated (Att) human rotavirus (HRV) Wa strain vaccine in a neonatal gnotobioti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 41 publications
(48 reference statements)
1
39
0
Order By: Relevance
“…IgM, IgG, and IgA HRV antibody geometric mean titers (GMTs) and total IgA concentrations in serum were measured by enzyme-linked immunosorbent assay (ELISA) pre-virHRV inoculation (PFMTD9 or PFMTD10/PID0), post-virHRV inoculation (PID9), and at the termination of the experiment (PID14) as described previously (16,21,74). The same parameters were measured in the small intestinal contents at PID14.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…IgM, IgG, and IgA HRV antibody geometric mean titers (GMTs) and total IgA concentrations in serum were measured by enzyme-linked immunosorbent assay (ELISA) pre-virHRV inoculation (PFMTD9 or PFMTD10/PID0), post-virHRV inoculation (PID9), and at the termination of the experiment (PID14) as described previously (16,21,74). The same parameters were measured in the small intestinal contents at PID14.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, pigs are outbred, eliminating the strain bias common in mouse model research. We have used the GF pig to study controlled exposure to microorganisms and physiologically relevant and economically feasible intervention strategies (15)(16)(17)(18)(19)(20)(21)(22). Recently, investigators have successfully transplanted GF pigs with human gut microbiota (23) and used this model to examine the effects of probiotics on human rotavirus (HRV) pathogenesis and immunity (24)(25)(26).…”
mentioning
confidence: 99%
“…The blocking effects of maternal antibodies have been demonstrated for both enteric and respiratory vaccines, such as RV (37)(38)(39), swine influenza (40,41), bovine respiratory syncytial virus (42), and bovine viral diarrhea virus (43)(44)(45). These studies have suggested that for live vaccines, the presence of maternal antibodies may result in low rates of seroconversion.…”
Section: Suppressive Effects Of Maternal (Passive) Antibodies On Immumentioning
confidence: 99%
“…However, studies have shown enhancement of active antibody responses by soluble antigen-antibody complexes in in vivo conditions for all subisotypes of IgG antibodies in mice (53). Vaccination studies have also shown enhancement of active antibody responses in the presence of lower titers of maternal antibodies (37,54,55). Several factors, such as age at vaccination, titer of maternal antibodies, type of vaccine [live, killed, or attenuated (including degree of attenuation)], dosage, number of doses, nature of antigen (carbohydrate or protein), use of adjuvant, and the methods used for determining antibody responses, may influence the outcome of immunization studies in neonates.…”
Section: Suppressive Effects Of Maternal (Passive) Antibodies On Immumentioning
confidence: 99%
See 1 more Smart Citation